SIMULASI NUMERIK KENDALI KAPAL CEPAT TAK BERAWAK UNTUK PEMETAAN IKAN - Andika Haryo Kusuma Putra (2020)
In this final project discusses the simulation of automation control and hull manufacturing on a fast boat that will be carried out for fish mapping. In this study collected a lot of literature from various sources about the system that exists on a ship, both in its control, motion, navigation, and the influence of the motion of the ship itself. This study uses a numerical simulation method with analytic software to simulate its motion. The experiment was carried out 3 times in forward motion, and 3 times in turn motion to measure the time needed for the ship to run in steady conditions. With the PID value for forward overshoot with values such as: 8.94%, 30.86%, and 40.60%, while turning overshoot is obtained, among others: 25.77%, 49.82%, and 61.15% Then the advanced settling time obtained includes: 0.91 seconds, 3.84 seconds, and 5.31 seconds. The settling time for turns is: 1,022 seconds, 0.85 seconds, and 0.84 seconds These values are obtained from the simulation graph of the three-doff formula for surge, sway, yaw.